Continuidades e rupturas no processo de trabalho dos marmoristas : 1890 1950 e os dias de hoje. - Moroni Filho, Elio (2006)
This work describes the similarities and differences in the work process of treating ornamental stones, comparing this against two periods of time (1890-1950 and the present time), the technological stages and work organization in marble and granite companies of the past and of the present. Data collection was based on various research sources and qualitative techniques (systematic direct observation and oral statements) and quantitative research (survey interviews). It was verified that the local marble and granite companies - since the end of the XIX century up until the present time - are installed in the mercantile establishments that operate in the third main stage of the productive cycle of the ornamental stones, elaborating final products from unrefined or polished slabs that are supplied by third parties. The semi-craft work organization and arduous work conditions seem to be conditioned to the technology employed by these companies. Along the XX century, local companies underwent technological improvements and upgrading, using new equipment and tools that increased efficiency of the final treating process. However, such technological changes did little to significantly improve work conditions and to eliminate predominant manual work with mechanical tools; although the work has been disassociated with partial craft work, the worker s skills remains the basis of the work process. However, the local companies have been incapable of modernizing their work units, not upgrading their systems with relation to available technologies worldwide. Mechanization and automation of the process, already incorporated by many companies in this sector, could modify the profile of the variables afore mentioned. Nevertheless, the small local companies are incapable of substituting or upgrading their equipments due to their low capitalization level at the rate the market develops and presents equipment.